2011
DOI: 10.1111/j.1741-2358.2011.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of denture‐cleaning methods based on the quantity of microorganisms adhering to a denture

Abstract: Examination of denture-cleaning methods based on the quantity of microorganisms adhering to a denture Objectives: To investigate effective denture-cleaning methods, we examined the relationships between the quantity of microorganisms adhering to dentures and the use of a denture brush and the frequency of use of a denture cleanser. Subjects and Methods: Denture plaque was collected from the mucosal surface of the examined dentures, which were 142 and 80 upper and lower complete dentures, respectively, worn by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 31 publications
4
46
0
5
Order By: Relevance
“…In terms of the quality of the oral microbial flora, the predominant microorganisms in this study were Streptococcus spp., Neisseria spp. and Candida spp., which is consistent with other results. The prevalence of Streptococcus spp., which were the most common microorganisms in this study, showed no significant differences depending on the type of prosthesis or presence of dry mouth.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In terms of the quality of the oral microbial flora, the predominant microorganisms in this study were Streptococcus spp., Neisseria spp. and Candida spp., which is consistent with other results. The prevalence of Streptococcus spp., which were the most common microorganisms in this study, showed no significant differences depending on the type of prosthesis or presence of dry mouth.…”
Section: Discussionsupporting
confidence: 93%
“…However, pouring specific culture media into a denture or impression allows for examination of only particular microorganisms, such as Candida spp. Therefore, examination of microbial flora is performed using a swab or spatula. In terms of the sampling area, Kashiwabara et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nishi et al [38] reported that daily soaking of dentures in a denture cleanser was effective method for reducing the quantities of microorganisms adhering to dentures. The guidelines outlined by the American College of Prosthodontics recommend that dentures should be cleaned daily by soaking and brushing with on effective, nonabrasive denture cleanser [39].…”
Section: Discussionmentioning
confidence: 99%
“…1 Daily denture brushing is recommended to reduce the amount of microorganisms adhering to the denture surface. 2 However, oral candidiasis can still occur in patients with predisposing factors, such as immunocompromised status, xerostromia, and age of the denture. 1 Moreover, advancing age is also a risk factor for dentureinduced stomatitis in elderly patients due to their reduced cell-mediated immunity that may lead to fungal infection.…”
Section: Introductionmentioning
confidence: 99%